2010
DOI: 10.1093/brain/awq041
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical location of effective deep brain stimulation electrodes in chronic cluster headache

Abstract: Deep brain stimulation of the posterior hypothalamus is a therapeutic approach to the treatment of refractory chronic cluster headache, but the precise anatomical location of the electrode contacts has not been clearly assessed. Our aim was to study the location of the contacts used for chronic stimulation, projecting each contact centre on anatomic atlases. Electrodes were implanted in a series of 10 patients (prospective controlled trial) in the so-called 'posteroinferior hypothalamus' according to previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 30 publications
3
80
0
4
Order By: Relevance
“…It has been questioned whether the stimulated area, according to the published stereotactic coordinates, indeed is the pHyp or is the adjacent mesencephalic gray. Recently Fontaine et al used the Schaltenbrandt atlas and a stereotactic threedimensional (3D) MRI atlas of the diencephalonmesencephalon junction to precisely pinpoint the electrode in ten hDBS patients who had the implant procedure according to the published coordinates (43). They observed that the hDBS electrodes (both in responders and nonresponders) were located posterior to the mamillary body and mamillo-thalamic fasciculus, usually defined as the caudal border of the hypothalamus.…”
Section: Mechanisms and Perspectives Of Hdbsmentioning
confidence: 99%
“…It has been questioned whether the stimulated area, according to the published stereotactic coordinates, indeed is the pHyp or is the adjacent mesencephalic gray. Recently Fontaine et al used the Schaltenbrandt atlas and a stereotactic threedimensional (3D) MRI atlas of the diencephalonmesencephalon junction to precisely pinpoint the electrode in ten hDBS patients who had the implant procedure according to the published coordinates (43). They observed that the hDBS electrodes (both in responders and nonresponders) were located posterior to the mamillary body and mamillo-thalamic fasciculus, usually defined as the caudal border of the hypothalamus.…”
Section: Mechanisms and Perspectives Of Hdbsmentioning
confidence: 99%
“…They may comprise a single needle bearing multiple contacts on its shaft [20,39] or a 10 9 10 matrix of single contact electrodes [19,36]. Successful penetrating electrodes are already available to humans, e.g., cochlear implants [40] and deep brain stimulator [10,17]. However, stable and long-term recording and stimulation remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…While Leone et al [3] think that DBS stimulates the posterior hypothalamus [3], Meyerson [24] and Burchiel et al [25] suggest that the stimulated volume reaches the periaqueductal gray. Fontaine et al [10] believe that the active contacts are located in a bridging zone between the hypothalamus and the mesencephalic gray matter, and Clelland et al [11] believe that they are located in the gray matter of the mesencephalic tegmentum. Akram et al [23] also place their target at the mesencephalic tegmentum, just anterior to the nucleus ruber.…”
Section: Discussionmentioning
confidence: 99%